Blue Banana dynamics and the perspective of its edges - Capoani, Luigi; Lakócai, Csaba; Imbesi, Cristoforo; Van Veen, Violetta (European Spatial Research and Policy, 2024)
This paper investigates the positioning of the UK and Northern Italy within the Blue Banana, which the literature considers as the productive core of Europe. We compare the main economic characteristics of the two regions with the rest of the Blue Banana by analysing several indicators, ranging from urbanisation and infrastructure development to unemployment, productivity, competitiveness, and attractiveness. Based on our findings, in terms of population, urbanisation, and infrastructure, the Blue Banana and the two edges are still an integral part of Europe’s core. However, in terms of employment structure, productivity, competitiveness and attractiveness, its significance can be questioned due to the weaker performance of Northern Italy and the negative effects of Brexit.